МЕТОДЫ ОПТИМИЗАЦИИ И ИНТЕНСИФИКАЦИИ ОБУЧЕНИЯ РУССКОМУ ЯЗЫКУ КАК ИНОСТРАННОМУ - Абдуллаева, Р.А. (SCIENCE and SOCIETY, 2025)
This article addresses the three main problems of teaching Russian language in non-linguistic environment: curricula and textbooks, the training of teachers of Russian language and teaching methods. It is concluded that it need new textbooks, in which must be implemented individually-oriented teaching Russian as a foreign language.